A State and Provincial Survey of Harvest Reporting and Data Collection Methods. Issue 2 (4th March 2017) - LaBonte, Andrew M.; Kilpatrick, Howard J.
ABSTRACT: This article explored state and provincial wildlife agency deer ( Odocoileus sp.) harvest data collection methods (in-person check stations [IPC], postal mail, telephone, and Internet harvest reporting [IHR]), and agency opinions about using hunter-provided data in making sound management decisions. We conducted an Internet survey of all U.S. and Canadian wildlife agencies' deer program coordinators to determine current methods used for harvest reporting. Among agencies, IHR was the most commonly used method (64%), followed by IPC (46%), telephone (41%), and mail-in kill cards (25%). An additional 13 states were in the process of providing telephone and IHR. Most agencies expressed confidence in data hunters provided and felt these data were important in helping make management decisions. Automated systems (e.g., telephone and IHR) may provide opportunities for hunters to easily report their harvest, thereby potentially increasing harvest reporting rates, eliminating manual data entry by staff, and allowing for immediate access to data.